Pengaruh Promosi, Literasi Keuangan dan Persepsi Risiko Terhadap Minat Menabung Emas Bank Syariah ABC Melalui Kesadaran Merek: The Influence of Promotion, Financial Literacy and Perceived Risk on The Saving Intention of Gold Saving Product in Bank Syariah ABC Through Brand Awareness Mediation - Handaru Wulan, Asvianti; Simanjuntak, Megawati; Taryana, Asep (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Gold savings products are unique products from sharia banking which have significant growth potential in Indonesia as seen from the increase in gold sales over the last 3 years. Based on previous research stated that promotion, financial literacy and risk perception are the factors that influence customers' saving intention in investment and services product in banking but there isn't any yet study examine the influence of those factors on gold savings products in sharia banking.Purpose: This study aims to analyze the influence of promotion, financial literacy and risk perception on the saving intention of gold savings product of Bank Sharia ABC both directly and through the mediation of brand awareness. Design/methodology/approach: This study uses the SEM-PLS (Structural Equation Modelling Partial Least Square) analysis method with a sample of 206 (two hundred and six) respondent which are customers of savings accounts who do not yet have a gold savings account at Bank Syariah ABCFindings/Result: This study show that promotion variable has a positive and significant influence on brand awareness of gold saving product. Meanwhile, promotion does not have a significant positive influence on the saving intention of gold saving product. Promotion has a positive and significant influence on the saving intention of gold saving product indirectly through the mediation of brand awareness variables (full mediation). As for the financial literacy, the variable has a positive and significant influence on brand awareness and the saving intention of gold saving product. The financial literacy variable also has a positive and significant influence on the saving intention of gold saving product indirectly through the mediation of brand awareness (partial mediation). Conclusion: The study also concluded that risk perception variable has a positive and significant influence on brand awareness of gold saving product. Meanwhile, risk perception does not have a significant positive influence on the saving intention of gold saving product. Risk perception variable has a positive and significant influence on the saving intention of gold saving product indirectly through the mediation of brand awareness variables (full mediation). The brand awareness variable has a positive and significant influence on the saving intention of gold saving product. So that, it can be said that if the brand awareness of customers is increase, the saving intention of gold saving product also increase.Originality/value (State of the art): Several previous studies have examined the influence of promotion, financial literacy and risk perceptions on the saving intention in investment and services product in banking, but there isn't any yet has specifically examined the influence of those factors on gold savings products in sharia banking. This study examine the influence of promotion, financial literacy and risk perceptions on the saving intention of gold saving product in sharia banking both directly and through the mediation of brand awareness. Keywords: brand awareness, financial literacy, promotion, risk perception, saving intention